FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENGGANTIAN KANTOR AKUNTAN PUBLIK SECARA SUKARELA - Andika Nugroho Sulistianto; Darsono Darsono (Diponegoro Journal of Accounting, 2015)
This research aims to provide empirical evidence about the factors that affect the replacement public accountant on a voluntary basis by the manufacturing companies listed on the indonesia stock exchange. Independent variables used in this study are: the audit opinion, financial distress, management changes, the size of the company and the company's growth was measured using two IE proxy changes in sales and changes in total assets.Object of research is the manufacturing companies listed on the indonesia stock exchange for 5 years (2009-2013) but for some variables needed data for the year was. Data collecting method which used in this research is method purposive sampling, that based on criterion which has been determined before. The dependent variable in this study was the replacement public accountant on a voluntary basis. Hypothesis in this research are tested by logistics regression analytical method.Result of this research indicates that variables having which significantly effect the replacement public accountant on a voluntary basisare audit opinion and management changes. In the other hand, other variables in this research like financial distress, company size, and companys growth don’t have significant effect on decision to do replacementof public accountant on a voluntary basis.